1991
DOI: 10.1126/science.1948029
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Structure of the GCN4 Leucine Zipper, a Two-Stranded, Parallel Coiled Coil

Abstract: The x-ray crystal structure of a peptide corresponding to the leucine zipper of the yeast transcriptional activator GCN4 has been determined at 1.8 angstrom resolution. The peptide forms a parallel, two-stranded coiled coil of alpha helices packed as in the "knobs-into-holes" model proposed by Crick in 1953. Contacts between the helices include ion pairs and an extensive hydrophobic interface that contains a distinctive hydrogen bond. The conserved leucines, like the residues in the alternate hydrophobic repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

58
1,321
3
8

Year Published

1993
1993
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,455 publications
(1,390 citation statements)
references
References 52 publications
58
1,321
3
8
Order By: Relevance
“…If true, we should be able to exchange the Bcr coiled-coil with another oligomerization domain and retain activation. We therefore replaced the N-terminal 63 amino acids of Bcr/1-509-Abl with a coiled-coil from a completely unrelated protein: the leucine zipper from the yeast transcription factor GCN4 (O'Shea et al, 1991). The C-terminal 34 amino acids of GCN4 which contain the leucine zipper domain were ®tted with a consensus eukaryotic translation initiation sequence and then fused in frame with the Bcr-Abl coding region (Figure 1, ZIP-Bcr/64-509-Abl).…”
Section: Resultsmentioning
confidence: 99%
“…If true, we should be able to exchange the Bcr coiled-coil with another oligomerization domain and retain activation. We therefore replaced the N-terminal 63 amino acids of Bcr/1-509-Abl with a coiled-coil from a completely unrelated protein: the leucine zipper from the yeast transcription factor GCN4 (O'Shea et al, 1991). The C-terminal 34 amino acids of GCN4 which contain the leucine zipper domain were ®tted with a consensus eukaryotic translation initiation sequence and then fused in frame with the Bcr-Abl coding region (Figure 1, ZIP-Bcr/64-509-Abl).…”
Section: Resultsmentioning
confidence: 99%
“…Intersubunit salt bridges at three such pairs of sites are observed in the crystal structure of the GCN4 leucine zipper (O'Shea et al, 1991;Ellenberger et al, 1992). One of the goals of this work was to assess the importance of these kinds of salt bridges in stabilizing the leucine zipper.…”
Section: The Importance Of Charged Residuesmentioning
confidence: 99%
“…The most extensively characterized leucine zipper is from the yeast transcriptional activator GCN4. Detailed structures have been determined by X-ray crystallography for both the leucine zipper domain (Kinemage 1; O'Shea et al, 1991) and the basic-region leucine zipper motif bound to DNA (Ellenberger et al, 1992). Structural properties of the GCN4 leucine zipper have also been studied in solution by two-dimensional NMR spectroscopy (Oas et al, 1990), amide proton exchange (Goodman & Kim, 1991), and biochemically using synthetic leucine zipper peptides (O'Shea et al, 1989a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Structural studies of synthetic peptides corresponding to the leucine zipper motif of GCN4 demonstrated that this domain assumes a coiled-coil 1461 structure of parallel helices (O'Shea et al, 1989a,b;Oas et al, 1990). The a-helical structure and parallel coiledcoil arrangement of this domain have been corroborated by two-dimensional (2D) 'H-NMR (Oas et al, 1990) and X-ray crystallographic data (O'Shea et al, 1991). The DNA binding domain of leucine zipper proteins is predominantly a basic region of approximately 30 amino acid residues located upstream of the leucine zipper motif.…”
mentioning
confidence: 92%